LincROR Mediates the Suppressive Effects of Curcumin on Hepatocellular Carcinoma Through Inactivating Wnt/β-Catenin Signaling - Shao, Jiang; Shi, Chuan-Jian; Li, Yun; Zhang, Feng-wei; Pan, Fei-fei; Fu, Wei-ming; Zhang, Jin-fang (Frontiers in Pharmacology, 2020)
As a leading cause of cancer related death in the world, hepatocellular carcinoma (HCC) continues to be attracted various attention in recent decades. The traditional Chinese herb has been practiced for thousands of years which provides the promising potential for the treatment of HCC. Curcumin, a bioactive ingredient derived from Curcuma longa, exhibits anti-tumor activity in various cancers. Although the effects of Curcumin on HCC has been elucidated, the underlying mechanism remains unclear. In the present study, Curcumin was demonstrated to inhibit the proliferation of HCC cells via inducing cell cycle arrest and apoptosis. Several previously reported lncRNAs related tumorigenesis were chosen for examination of their expression profilings, and lincROR was the most down-regulated in the Curcumin-treated HCC cells. Furthermore, Curcumin was found to decrease the β-catenin expression and induce the inactivation of Wnt/β-catenin signaling. Therefore, Curcumin suppressed tumor growth through a lincROR/β-catenin regulatory pattern. In conclusion, our results demonstrated that Curcumin suppressed the cell proliferation via down-regulation of lincROR and inactivation of Wnt/β-catenin signaling, suggesting that it may be a potential anti-cancer candidate for the HCC patients with activated Wnt/β-catenin signaling.